(untitled) (Research, Society and Development, 2021)
Cancer is a disease characterized by the uncontrolled multiplication and proliferation of genetically modified cells, being one of the main causes of death in the world. The therapy available to date is the use of chemotherapeutics that have adverse effects on patients, and, in addition, are non-specific as they affect normal cells. Thus, the search for information about molecules with anticancer activity becomes a relevant tool for mapping and biotechnological applications. Thus, the objective was to carry out a scientific and technological survey of the plant Aeschynomene denticulata with emphasis on essential oil and its anticancer activity in articles and patents indexed in national and international platforms. For this, keywords and combinations of terms with the Boolean operator AND were used for the search: “Aeschynomene denticulata”, “Antitumor”, “Cancer”, “Essential oil” and “Metastasis”. The results show that most of the articles and patents use the descriptor Aeschynomene denticulata. In the scientific databases, PubMed, Scielo and Scopus presented 3, 7 and 23 articles, respectively. In terms of technology, the only one to present patents was EPO, in a total of 23 works, considering Germany highlighted in the protection of research involving Aeschynomene denticulata. When used in combination of descriptors, no articles and/or patents were found. Thus, it is concluded that there are few studies and technologies developed with the plant species and that there are no works involving applications of essential oil in cancer.